THE INFLUENCE OF FINANCIAL LITERACY AND ENTREPRENEURIAL MOTIVATION ON INTEREST IN STARTING AN INDEPENDENT BUSINESS AMONG SATYAGAMA UNIVERSITY STUDENTS - Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Didi Sukardi; Murdiyono Murdiyono (Nusantara Hasana Journal, 2023)
This study aims to analyze the influence of financial literacy and entrepreneurial motivation on the interest in starting an independent business among Satyagama University students. Financial literacy is an important skill for students in managing finances, understanding business risks, and making the right economic decisions. Meanwhile, entrepreneurial motivation plays a role in encouraging students' courage, creativity, and desire to create an independent business. The study used a quantitative approach with a survey method through the distribution of questionnaires to active students of Satyagama University. The data analysis technique used multiple linear regression to determine the partial and simultaneous effects between variables. The results showed that financial literacy and entrepreneurial motivation have a positive and significant effect on the interest in starting an independent business. The better the students' understanding of financial management and the higher their entrepreneurial motivation, the higher the students' interest in starting an independent business. This research is expected to be a consideration for universities in improving entrepreneurship education and student financial literacy.